Short-term nitrogen dynamics are impacted by defoliation and drought in Fagus sylvatica L. branches. (16th February 2019) - Chuste, Pierre-Antoine; Massonnet, Catherine; Gérant, Dominique; Zeller, Berndt; Levillain, Joseph; Hossann, Christian; Angeli, Nicolas; Wortemann, Rémi; Bréda, Nathalie; Maillard, Pascale
Abstract: The predicted recurrence of adverse climatic events such as droughts, which disrupt nutrient accessibility for trees, could jeopardize the nitrogen (N) metabolism in forest trees. Internal tree N cycling capacities are crucial to ensuring tree survival but how the N metabolism of forest trees responds to intense, repeated environmental stress is not well known. For 2 years, we submitted 9-year-old beech ( Fagus sylvatica L.) trees to either a moderate or a severe prolonged drought or a yearly removal of 75% of the foliage to induce internal N cycling changes. During the second year of stress, in spring and summer, we sprayed 15 N-urea on the leaves (one branch per tree). Then, for 14 days, we traced the 15 N dynamics through the leaves, into foliar proteins and into the branch compartments (leaves and stems segments), as well as its long-distance transfer from the labeled branches to the tree apical twigs. Defoliation caused a short- and mid-term N increase in the leaves, which remained the main sink for N. Whatever the treatment and the date, most of the leaf 15 N stayed in the leaves and was invested in soluble proteins (60–68% of total leaf N). 15 N stayed more in the proximal part of the branch in response to drought compared with other treatments. The long-distance transport of N was maintained even under harsh drought, highlighting efficient internal N recycling in beech trees. Under extreme constraints creating an N and water imbalance, compensation mechanisms operated at the branch level in beech trees and allowed them (i) to maintain leaf N metabolism and protein synthesis and (ii) to ensure the seasonal short- and long-distance transfer of recycled leaf N even under drastic water shortage conditions.